A measurement model of the determinants of financial exclusion among micro-entrepreneurs in Ilorin, Nigeria - Adeyemi, Adewale Abideen; Pramanik, Ataul Huq; Mydin Meera, Ahamed Kameel (IIUM Institute of Islamic Banking and Finance, 2012)
This study investigated the various factors that impede both the access to and use of the requisite financial resources for entrepreneurial development in Ilorin, Nigeria. Data was collected via a survey questionnaire administered on Muslim micro-entrepreneurs in the study area. A measurement model using the structural equation modelling approach was adopted. The paper concluded that both the voluntary and involuntary financial exclusion factors significantly account for financial exclusion among the respondents. However, voluntary exclusion signals a relatively serious problem. This is because it is a reflection of lack of use, rather than lack of access to financial services by the Muslim poor. In this regard, religious consideration as well as debt phobia as a reflection of the presence of Islam in the area had statistically significant factor loadings. Recommendations were also offered.